2003
DOI: 10.1007/s00330-002-1686-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the radiographer on the pain felt during mammography

Abstract: Mammography is the only useful examination in screening for breast cancer. Mortality from breast cancer can be reduced if women go regularly for a screening mammography. Moreover, it is still the key examination in diagnosis of breast diseases and in the follow-up of patients treated for breast cancer. Pain with mammography can deter women from going for regular screening or follow-up; therefore, it is important to reduce pain experience or discomfort from mammography. In this study we evaluate the impact of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 25 publications
1
20
1
2
Order By: Relevance
“…One such (Van Goethem et al . ) not only sought the opinions of patients on staff, but also the views of radiographers on patients, and found poor correlation between the radiographers' views about the patients' experience and patients' own accounts.…”
Section: Resultsmentioning
confidence: 99%
“…One such (Van Goethem et al . ) not only sought the opinions of patients on staff, but also the views of radiographers on patients, and found poor correlation between the radiographers' views about the patients' experience and patients' own accounts.…”
Section: Resultsmentioning
confidence: 99%
“…However, the conduct of the staff may affect this experience (Morris, 2015; Whelehan, Evans, & Ozakinci, 2017). Hence, the importance of staff’s concern for the women’s feeling of comfort in an exposed situation cannot be underestimated (Van Goethem et al, 2003). Interestingly, the attitude towards one’s own, as well as others’ decisions to participate, is often described as a certainty and may mirror the norm of acceptance when offered a benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings support existing contentions that there is considerable variation in the pain experienced during mammography (Davey, ), and that pain can act as a deterrent to screening participation (Whelehan et al., ). One strategy shown to help reduce perceived pain and discomfort is for mammographers to enable women to feel that they are in control, as far as possible (van Goethem et al., ; Poulos & Llewellyn, ). While the mammographers believed that empowering clients was important, they sometimes experienced limitations in the extent to which it was feasible and found themselves taking a more authoritarian approach.…”
Section: Discussionmentioning
confidence: 99%
“…While the results for pain reduction were promising, the study was preliminary and further work would be needed before the intervention, which would involve equipment modification, could be implemented. Observational studies have identified non‐physical aspects of mammographic practice, largely concerning staff communication and caring skills, which can reduce reported pain and improve client satisfaction (Almog, Hagoel, Tamir, Barnett, & Rennert, ; van Goethem et al., ). However, while mammography training and culture may acknowledge these findings, they have not been translated into formal interventions.…”
Section: Introductionmentioning
confidence: 99%